THEMATIC LEARNING AND ITS APPLICATION IN THE LEARNING PROCESS - Eka Zulfianita (Fenomena, 2022)
Cooperative learning arises from the concept that learners will more easily find and understand complex concepts if they discuss them with their friends. Students regularly work in groups to help each other solve complex problems. This type of research is a case study. This conclusion research can be that the planned implementation of cooperative learning model type STAD includes; 1) the teacher prepares the program of the semester and syllabus compiled together a team of the KKG at the beginning of the semester. 2) preparing lesson plans. Making model cooperative type STAD includes 1) The Beginning, 2) the Core Activities, and 3) The End of the Activity. At the same time, the impact of the STAD Cooperative learning model on the learning theme in improving students' learning outcomes has a positive and negative effect. Pembelajaran kooperatif muncul dari konsep bahwa peserta didik akan lebih mudah menemukan dan memahami konsep yang sulit jika mereka saling berdiskusi dengan temannya. Peserta didik secara rutin bekerja dalam kelompok untuk saling membantu memecahkan masalah-masalah yang kompleks. Jenis penelitian ini adalah  kulaitatif dengan pendekatan studi kasus. Dari hasil penelitian ini dapat dismpulkan bahwa perencanaan penerapan model pembelajaran kooperatif tipe STAD diantaranya; 1) Guru menyiapkan program semester dan silabus yang disusun bersama tim KKG pada awal semester. 2) Menyusun RPP. Penerapan model kooperatif tipe STAD dengan meliputi: 1) Kegiatan Awal  2) Kegiatan Inti  3) Kegiatan Akhir. Sedangkan dampak penerapan model pembelajaran Kooperatif Tipe STAD pada pembelajaraan tematik dalam meningkatkan hasil belajar peserta didik memiliki dampak positif dan negatif.